INVASIVE ALIEN PLANT SPECIES IN THE RIPARIAN AREAS OF NORTHERN SAMAR, PHILIPPINES - Joey Liza Abobo; Joy Esmabe; Marjurie Baldoza; Princess Cerbito; John Mark Garbo; Ramon Philip Bacayo; Chitlyn Tenedero; Maricar Lameda; Rica Joy Saavedra; Cresil Turbanada; Roanne Romeroso (SEAMEO BIOTROP, 2025)
ARTICLE HIGLIGHTS- A pioneering study of invasive alien plant species in the riparian areas of Northern Samar- Species composition, endemism, and conservation status of introduced species- Out of 65 introduced species, 32 were listed as invasiveABSTRACTRiparian areas are highly dynamic and naturally disturbed, making them particularly susceptible to invasion. Invasive Alien Plant Species (IAPS) are widely distributed in these areas due to the favorable environmental conditions that support their growth and persistence. This study is a pioneering effort to document the invasive alien plant species thriving in the riparian zones of Allen, Biri, Catarman, Gamay, Mapanas, Laoang, Lapinig, Las Navas, and Pambujan in Northern Samar. Sampling was conducted from March to December 2023. Six transect lines, each measuring two kilometers per site, were established in the riparian areas to identify existing invasive alien plants. In total, 60 transect lines were set up across all sampling areas. As a result, 65 introduced plant species belonging to 24 families and 56 genera were documented in the riparian areas of Northern Samar. The families with the highest number of species were Poaceae (13 spp.), Asteraceae (12 spp.), Cyperaceae, Fabaceae, and Lamiaceae (5 spp. each). The remaining families had fewer than five species each. The most common invasive plant species recorded was Psidium guajava L., which was present in all sampling areas. Based on life forms, the study identified two tree species, 17 shrubs, three vines, one epiphyte, and 42 herbs. Conservation status was determined using the latest IUCN and DENR listings (2017–11). One taxon was classified as Data Deficient, 32 as Least Concerned, and the remaining species as Not Evaluated. In contrast, no taxa were assessed in the DENR 2017–11 listing. Furthermore, of the 65 introduced plant species documented, 10 were recorded as invasive in the Global Invasive Species Database, while 22 were listed in the Global Register of Introduced and Invasive Species Database. Although invasive alien species have long been recognized as posing serious threats to human health, forestry, agriculture, fisheries, and natural biodiversity, no comprehensive assessment of their status, trends, causes, impacts, management, and governance issues has been conducted worldwide. Thus, this study aimed to supplement existing data on invasive plants and assist policymakers in developing policy frameworks for managing invasive alien plant species to mitigate their impacts on human health and the environment.